Best Answer

x2-5-4x2+3x = 0

-3x2+3x-5 = 0 or as 3x2-3x+5 = 0

Q: Can you put the equation x2 - 5 -4x2 plus 3x equals 0 in the form ax2 plus bx plus c equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

NO,because in quadratic equation highest power of a variable is 2. e.x. 4x2-20x+10=0.

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.

Fraction: 16/2 equation, 4x2

The one which says: y2 = 4 - 4/25 x2

Y

Related questions

The discriminant is 33.

4x2 plus 3=11

2.

y=4x2+3x+8

No. [ y = 4x2 ] is a quadratic equation.

The expression is likely 4x2 - 36x +81 which is the same as (2x - 9)(2x - 9) or (2x - 9)2

NO,because in quadratic equation highest power of a variable is 2. e.x. 4x2-20x+10=0.

Solution: x = 1/4 and x = -3.

The equation y = 4x^2 + 5 is a parabola

yes

Using the quadratic equation formula:- x = -0.5447270865 or x = 2.294727086

4x2+49x+90 = (4x+9)(x+10) when factored